Review: Decentralised governance: crafting effective democracies around the world edited by Jean-Paul Faguet and Sarmistha Pal (Commonwealth Journal of Local Governance, 2024)
The premise for this book is that for more than six decades decentralisation has been one of the most powerful reform movements across the world, and that – under the right conditions – decentralised systems produce more effective public services and are more democratic. However, despite the breadth and depth of the book’s analysis, this reviewer emerged little wiser about precisely what those ‘right conditions’ might be, and wondering how often decentralisation of some sort is the ‘right’ idea in the first place.